Green Synthesis of Trimetallic Oxides (CuO-ZnO-MnO) Nanoparticles using Ocimum basilicum Aqueous Leaves Extract: Characterization and Antibacterial Activity - Fouzia Majeed; Syeda Shaista Gillani; Iram Bashir (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2024)
Metal oxides nanoparticles (NPs) are becoming more and more significant day by day in a variety of fields, due to their unique physical, biological and chemical properties that have made them popular. In the current study, we developed a green chemistry method that is easy to use, cost-effective, safe for the environment, and produces trimetallic oxide (CuO-ZnO- MnO) nanoparticles using an aqueous leaves extract of Ocimum basilicum. The sequential reduction of zinc chloride, manganese chloride, and copper chloride solutions resulted in the production of trimetallic oxide (ZnO-MnO-CuO) nanoparticles within 5 minutes at 35 °C, indicating a faster reaction rate than the chemical techniques used before for such synthesis.Trimetallic oxide nanoparticles (NPs) were charecterized by FTIR, SEMEDX, XRD, and UV-visible spectropic techniques. A characteristic Surface Plasmon Resonance (SPR) band to confrm trimetallic oxide nanoparticles (NPs) synthesis was observed at 450 nm of λ light by UV–Visible spectrophotometer. There were noticeable peaks in the FTIR spectra which confirmed the presence of variuos functional groups in the trimetallic oxide NPs. SEM results showed the shape and polydispersive nature of the NPs, the existence of Mn, Cu, Zn, and O atoms was confirmed by EDX. The findings of the XRD results also confirmed the synthesis of nanoparticles. Synthesized trimetallic oxide (CuO-ZnO-MnO) nanoparticles were screened for antibacterial activity against Escherichia coli (Gram-negative) and Staphylococcus aureus (Gram-positive). The agar well diffusion assay revealed that trimetallic oxide (CuO-ZnO-MnO) nanoparticles have the highest efficacy against Staphylococcus aureus. As a result, trimetallic oxide nanoparticles may be effective antibacterial agents in the pharmaceutical sector.